An Uncommon Procedure for a Rare Ailment: Massive Bronchoalveolar Lavage in a Patient with Pulmonary Alveolar Proteinosis - Belgin Samurkaşoğlu; Behiye Akkalyoncu; Fatma Ulus; Mehtap Tunç; Özlem Çakır; Polat Pehlivanoğlu; Şaziye Şahin; Hilal Günal Sazak (Balkan Medical Journal, 2012)
As a rare procedure, massive bronchoalveolar lavage (MBAL) is a large-volume lavage which necessitates general anesthesia and one-lung ventilation (OLV). During MBAL isotonic saline is instilled into one lung and drained through one lumen of a double-lumen tube. MBAL is the most effective treatment for symptomatic pulmonary alveolar proteinosis (PAP). A 27-year-old male with PAP was scheduled for therapeutic MBALs. After standard preoxygenation, monitoring and anesthesia induction, a double-lumen tube was placed. Tube position was verified by a fiberoptic bronchoscope. The internal jugular vein, radial and pulmonary arteries were cannulated. A temperature probe and foley catheter were inserted. The nonventilated lung was filled with 1000 mL saline and then drained in each session. The left and right lung were lavaged with an interval of 2 weeks. A total of 20 L saline was used in each MBAL without retention. MBALs were terminated after the effluent became clear. Duration of the left and right MBALs were 325 and 275 minutes, respectively. Despite increased shunt fraction, oxygenation was within acceptable limits during OLV. The trachea was extubated in the operating room uneventfully after each MBAL. The patient’s clinical and laboratory findings were evidently improved. Consequently, if proper conditions are provided, MBAL is safe and beneficial despite its risks and the long duration.